Conversion of Plastic Surgery meeting abstract presentations to full manuscripts: a brazilian perspective - RAFAEL DENADAI; ANDRÉ SILVEIRA PINHO; HUGO SAMARTINE JÚNIOR; RODRIGO DENADAI; CASSIO EDUARDO RAPOSO-AMARAL (Revista do Colégio Brasileiro de Cirurgiões)
ABSTRACT Objective: to assess the conversion rate of Plastic Surgery meeting abstract presentations to full manuscript publications and examine factors associated with this conversion. Methods: we assessed the abstracts presented at the 47th and 48th Brazilian Congresses of Plastic Surgery by cross-referencing with multiple databases. We analyzed the Abstracts' characteristics associated with full manuscript publications. Results: of the 200 abstracts presented, 50 abstracts were subsequently published in full, giving the conference a conversion rate of 25%. The mean time to publish was 15.00±13.75 months. In total, there were 4.93±1.63 authors per abstract and 67.8±163 subjects per abstract; 43.5% of the abstracts were of retrospective studies; 69% comprised the plastic surgery topics head and neck, and chest and trunk, and 88.5% had no statistical analysis. Overall, 80% of the manuscripts were published in plastic surgery journals, 76% had no impact factor and 52% had no citations. Bivariate and multivariate analyses revealed the presence of statistical analysis to be the most significant (p<0.05) predictive factor of conversion of abstracts into full manuscripts. Conclusion: the conversion rate found from this bibliometric research appeared a bit lower than the conversion trend of international plastic surgery meetings, and statistical analysis was a determinant of conversion success.